Hadis - hadis Mukhtalif tentang Pakaian dan Perhiasan - Muhammad Iqbal (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Mukhtalif Hadith teaching has received serious attention since Sahabah era, which becomes the main reference of any issues after the Prophet. Studies on the contradict traditions is very important for students of hadith. There is no one good in this field, except the priests of hadith who have sharp analysis. Several of mukhtalif traditions have been compiled by scholars in special books. It has been written through the History, the scholar who pioneered the collection activity are Imam al-Syafi`i in his book Ikhtilaf al-Hadith, Ibn Qutaibah with his book Ta'weel Mukhtalif al-Hadith, Al-Thahawi with the title of his book Musykil al-Asar, Ibn Khuzaimah, Ibn Jarir and Ibn al-Jauzi.The scholars agreed that the contradict traditions must be resolved, so there is no more quarrel among people. However, the scholars may have different opinion in settling this case. seem contradictory conflict must be resolved so there goes that. Only in settling the conflict, scholars differed.